Using the Technology Available in the Learning Resource Centres (LRCs) in the Kingdom of Saudi Arabia: Arabic Language Teachers' Perceptions - Al-Qahtani, Nafal; Al-Qahtani, Rabee (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the degree of using educational technologies by Arabic language teachers in learning resource centers in Bisha province in Saudi Arabia, and to identify the statistical differences at the level of significance (α≤.05) in the degree of theirs implementing for educational techniques according to (Experience, educational qualification and educational stage) variables. The study followed the descriptive-analytical method and was applied to a population consisted of (450) Arabic language teachers, and its sample was limited to (159) teachers. For data collection, the researcher used a questionnaire consisting of six dimensions (design, use, management, evaluation, technical competencies and thinking development, production) with 50 phrases distributed on these dimensions. The study came out with the following results: The arithmetic means of the degree of using the technical competences by Arabic language teachers of on the tool was (2.64), and a percentage of (66.00%). The dimension with the highest degree of technical competences using was the design dimension with an arithmetic mean of (2.93), and a percentage (73.25%), followed by use's dimension with an average arithmetic (2.75), and a percentage of (68.75%). It was followed by management's dimension in the third place with an arithmetic mean of (2.74), and percentage (68.5%), followed by evaluation's dimension fourth place with an average of (2.71), and a percentage (67.75%). the technical competencies and thinking development dimension came in the fifth with an arithmetic mean (2.45), and a percentage (60.25%), and finally production's dimension in seventh place with arithmetic mean of (3.64), and percentage (66%). The results also indicated that there are differences between the arithmetic averages of Arabic language teachers' estimates in Bisha governorate to the extent of the exercise of technical competencies due to experience and scientific qualification variables. It also showed that there are differences between the arithmetic averages of Arabic language teachers' estimates in the Jouf region to the extent of technological competencies using due to education level variable. In the light of the results of the study, the researcher concluded that the need to Engage Arabic language teachers in specialized training courses in the fields where their performance has been medium.
Keywords: Arabic language; Educational Techniques; Learning Resource Centers; Bisha Governorate